Adipophilin: roles in physiology and pathology - Li, Feng-Zeng; Fang, Sheng (Journal of clinical pathology, 2023)
Adipophilin (ADRP/ADPH/PLIN2), an adipocyte differentiation-related protein, is highly expressed at a very early time during the differentiation of adipocytes. It assists in the formation and maintenance of intracellular lipid droplets and plays a role in regulating the physiological functions of the body. More and more studies indicate that it is involved in the occurrence and development of a variety of glycolipid metabolic diseases and tumours. In this review, we comprehensively stated the expression and functions of adipophilin and introduced its roles in physiology and pathology.